The Surgeon and Surgery in the Cinematic Poetics of the Thaw - Nyagolova, Natalia (Slavica, 2026)
The figure of the doctor occupies a distinctive place in Thaw cinema. This type of character embodies the moral maximalism of the Shestidesyatniki (the Sixties generation) and their new attitude toward health and the human body but also assumes the features of one of the era’s most pivotal heroes. The doctor is depicted as a laconic and decisive representative of the intelligentsia who opposes “the most harmful social elements” – bureaucrats and philistines. The hero also retains a certain degree of social isolation (an unstable personal life, reservedness, abruptness, and intransigence). Among all medical specialties, prominence on the screen is accorded to surgery, and the performance of complex operations frequently serves as the climax in many Thaw-era films. The paper examines the artistic projections of this particular medical sphere through the analysis of the films Heart beats Again (1956, dir. A. Room), My dear man (1958, dir. I. Kheifits), Colleagues (1962, dir. A. Sakharov), and Degree of risk (1968, dir. I. Averbakh). It accounts for the semantic and visual variations of the theme in war films of the period, as well as the specific representation of the surgeon in the cinema of the Union republics of the USSR (the Baltics and Central Asia). The text also makes an attempt to trace the main periods in the Thaw ideology – from films centered on re-education and “finding the right path,” through the pathos of “Rousseauian realism,” to the “Hamlet-type” surgeons in the cinema of the late 1960s.